Textured ceramic, preparation method thereof and capacitor
The high-end fiber-like barium titanate is synthesized through a hydrothermal ion exchange mechanism, and textured ceramics with high dielectric properties are prepared by texture casting and sintering processes, which solves the problem of difficulty in preparing high-oriented piezoelectric ceramics for capacitors in the prior art, and achieves higher capacitance and smaller volume.
Patent Information
- Application Number
- CN202411960810.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-11
AI Technical Summary
The prior art is difficult to prepare high-oriented piezoelectric ceramics for capacitors using template grain growth method, and fibrous barium titanate is difficult to meet the texture requirements.
Through the hydrothermal ion exchange mechanism, fibrous barium titanate with a high length diameter ratio and a small grain size are synthesized in the stirring state. Textured casting and sintering processes are used to prepare textured ceramics with a surface with a axis [001] orientation and a cross-section with a axis [100] orientation.
The high dielectric performance improvement rate of textured ceramics is achieved, reaching 31%-60%, and a higher capacity is achieved in capacitors without significantly increasing volume. It is suitable for electronic devices with limited space.
Smart Images

Figure CN119797937A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of dielectric ceramics, and in particular to a textured ceramic and a preparation method thereof, and a capacitor. Background Art
[0002] Currently, most reports on textured ceramics focus on the template grain growth method. Some people have proposed using flaky powder as a template to prepare highly oriented piezoelectric ceramics. However, due to the limitations of the capacitor preparation process, the template grain growth method is difficult to apply to capacitors.
[0003] As an important nanomaterial, fibrous barium titanate has a high aspect ratio and special crystallographic orientation, and can be used in electronic devices such as capacitors and sensors. However, the currently prepared fibrous barium titanate is difficult to meet the requirements of texturing. Summary of the invention
[0004] The applicant found that there is a large difference in the dielectric constant of tetragonal barium titanate single crystal in the a direction and c direction. At room temperature, the dielectric constant in the a direction is 2920, and the dielectric constant of the c axis is 168. The dielectric constant of the a axis is about 10.7 times that of the c direction. The dielectric constant of non-single crystal isotropic spherical barium titanate at room temperature is 1800. If a-axis
[100] preferentially oriented barium titanate ceramics are prepared by fibrous barium titanate, its dielectric constant can reach 1.5 times or more of that of non-single crystal isotropic spherical barium titanate. And because fibrous barium titanate has a lower particle size and a higher dielectric constant and is easy to achieve a high ceramic filling degree, it can achieve higher capacitance without significantly increasing the volume, so it has great potential in the application of ultra-thin multilayer ceramic capacitors.
[0005] The present application provides a textured ceramic and a preparation method thereof, wherein the surface of the textured ceramic presents a c-axis
[001] orientation and the cross section presents an a-axis
[100] orientation, and the dielectric performance of the a-axis cross section is improved by 31%-60%. When the textured ceramic is prepared as a capacitor, a higher capacitance is achieved without significantly increasing the volume.
[0006] In a first aspect, an embodiment of the present application provides a method for preparing a textured ceramic, the method comprising:
[0007] Performing a first hydrothermal reaction on a titanium source and a sodium source to obtain a sodium trititanate precursor;
[0008] Under stirring, a sodium trititanate precursor and a barium source are subjected to a second hydrothermal reaction to obtain fibrous barium titanate;
[0009] The fibrous barium titanate is prepared into a slurry and cast into a film to obtain a fiber film, wherein the fibrous barium titanate is oriented in the fiber film;
[0010] The fiber membrane is subjected to isostatic pressing and sintering to obtain textured ceramics.
[0011] As an optional embodiment, the stirring speed during the second hydrothermal reaction is no more than 1000 r / min; and / or
[0012] The aspect ratio of the fibrous barium titanate is 16 to 19; and / or
[0013] The grain size of the fibrous barium titanate is 50 nm to 56 nm.
[0014] As an optional embodiment, the titanium source includes titanium dioxide, and the crystal form of the titanium dioxide includes at least one of anatase phase, rutile phase or brookite phase; and / or
[0015] The sodium source comprises a sodium hydroxide solution having a molar concentration of 10 mol / L to 12 mol / L; and / or
[0016] The temperature of the first hydrothermal reaction is 200°C to 220°C; and / or
[0017] The time of the first hydrothermal reaction is 48 h to 72 h.
[0018] As an optional embodiment, the barium source includes a barium hydroxide solution, and the molar concentration of the barium hydroxide solution is 0.05 mol / L to 0.2 mol / L; and / or
[0019] The molar ratio of barium in the barium source to titanium in the sodium trititanate precursor is 1 to 1.2:1; and / or
[0020] The temperature of the second hydrothermal reaction is 150°C to 210°C; and / or
[0021] The time of the second hydrothermal reaction is 0.5h to 16h.
[0022] As an optional implementation, preparing the fibrous barium titanate into a slurry includes ball-milling the fibrous barium titanate, an organic solvent, a dispersant, and a plasticizer to obtain a slurry, and the ball-milling time of the ball-milling is 6 hours to 12 hours.
[0023] As an optional embodiment, the scraper height of the film casting is 80 μm to 120 μm; and / or
[0024] The casting speed of the cast film is 6 mm / s to 50 mm / s.
[0025] As an optional embodiment, the pressure of the isostatic pressing treatment is 65MPa to 70MPa; and / or
[0026] The heating rate of sintering is 5°C / min to 10°C / min; and / or
[0027] The sintering temperature is 1200°C to 1400°C; and / or
[0028] The sintering holding time is 2h to 3h.
[0029] In a second aspect, an embodiment of the present application provides a textured ceramic, which is produced by the method provided in the first aspect.
[0030] As an optional embodiment, the surface preferred orientation of the textured ceramic is c-axis
[001] , and the orientation degree of the c-axis is 15% to 24%; and / or
[0031] The preferred cross-sectional orientation of the textured ceramics is a-axis
[100] , and the orientation degree of the a-axis is 15% to 21%.
[0032] In a third aspect, an embodiment of the present application provides a capacitor, which includes the textured ceramic provided in the second aspect.
[0033] The above technical solution provided by the embodiment of the present application has the following advantages compared with the prior art:
[0034] The method provided in the embodiment of the present application utilizes a hydrothermal ion exchange mechanism to synthesize fibrous barium titanate with a high aspect ratio and a small grain size under stirring, and then performs texture casting and sintering. The surface of the textured ceramic obtained presents a c-axis
[001] orientation, and the cross section presents an a-axis
[100] orientation, and the dielectric performance of the a-axis cross section is improved at a large rate. Moreover, the fibrous barium titanate dielectric material allows capacitors to be constructed in a cross-sectional dominant direction, thereby achieving higher capacitance without significantly increasing the volume, and is particularly suitable for electronic devices with limited space. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the drawings required for use in the embodiments will be briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present application and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without paying creative work.
[0036] Figure 1 A flowchart of a method provided in an embodiment of the present application;
[0037] Figure 2 XRD spectrum (left) and SEM spectrum (right) of the sodium trititanate precursor provided in Preparation Example 1 of this application;
[0038] Figure 3 XRD spectra of products with different barium hydroxide concentrations provided in Preparation Example 2, Preparation Example 3, and Preparation Example 4 of this application;
[0039] Figure 4SEM images of products with different barium hydroxide concentrations provided for Preparation Example 2 (left), Preparation Example 3 (middle), and Preparation Example 4 (right) of this application;
[0040] Figure 5 XRD and SEM spectra of the reaction product provided for Preparation Example 5 of this application (no stirring during the reaction process);
[0041] Figure 6 The surface and cross-sectional XRD patterns of the textured ceramic (sintered at 1350° C.) provided in Example 1 of the present application;
[0042] Figure 7 The surface and cross-sectional XRD patterns of the textured ceramic (sintered at 1400° C.) provided in Example 2 of the present application;
[0043] Figure 8 Surface and cross-sectional XRD patterns of the spherical barium titanate ceramic (sintered at 1350° C.) provided in Comparative Example 1 of the present application. DETAILED DESCRIPTION
[0044] The embodiments of the present application will be described in detail below in conjunction with the examples, but it will be appreciated by those skilled in the art that the following examples are only used to illustrate the present application and should not be considered as limiting the scope of the present application. In the examples, if specific conditions are not specified, they are carried out according to normal conditions or the conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0045] Fibrous barium titanate, as an important nanomaterial, has a high aspect ratio and special crystallographic orientation and can be used in electronic devices such as capacitors and sensors.
[0046] The applicant found that there is a large difference in the dielectric constant of tetragonal barium titanate single crystal in the a direction and c direction. At room temperature, the dielectric constant in the a direction is 2920, and the dielectric constant of the c axis is 168. The dielectric constant of the a axis is about 10.7 times that of the c direction. The dielectric constant of non-single crystal isotropic spherical barium titanate at room temperature is 1800. If a-axis
[100] preferentially oriented barium titanate ceramics are prepared by fibrous barium titanate, its dielectric constant can reach 1.5 times or more of that of non-single crystal isotropic spherical barium titanate. And because fibrous barium titanate has a lower particle size and a higher dielectric constant and is easy to achieve a high ceramic filling degree, it can achieve higher capacitance without significantly increasing the volume, so it has great potential in the application of ultra-thin multilayer ceramic capacitors.
[0047] The present application intends to provide a textured ceramic, whose surface presents a c-axis
[001] orientation and whose cross section presents an a-axis
[100] orientation, and the dielectric performance of the a-axis cross section is improved by 31%-60%. When prepared as a capacitor, a higher capacitance is achieved without significantly increasing the volume.
[0048] Figure 1 For a flowchart of the method provided in the embodiment of the present application, please refer to Figure 1 The present invention provides a method for preparing a textured ceramic. The method comprises:
[0049] S1. subjecting a titanium source and a sodium source to a first hydrothermal reaction to obtain a sodium trititanate precursor;
[0050] In some embodiments, the titanium source includes titanium dioxide, and the crystalline form of the titanium dioxide includes at least one of anatase phase, rutile phase, or brookite phase.
[0051] In some embodiments, the sodium source includes a sodium hydroxide solution, and the molar concentration of the sodium hydroxide solution is 10 mol / L to 12 mol / L. Exemplarily, the molar concentration of the sodium hydroxide solution can be 10 mol / L, 10.5 mol / L, 11 mol / L, 11.5 mol / L, 12 mol / L, etc., and it can also be any value within the range of 10 mol / L to 12 mol / L.
[0052] In some embodiments, the temperature of the first hydrothermal reaction is 200° C. to 220° C. For example, the temperature of the first hydrothermal reaction can be 200° C., 205° C., 210° C., 215° C., 220° C., etc., or any value within the range of 200° C. to 220° C.
[0053] In some embodiments, the time of the first hydrothermal reaction is 48 hours to 72 hours. Exemplarily, the time of the first hydrothermal reaction can be 48 hours, 50 hours, 52 hours, 54 hours, 56 hours, 58 hours, 60 hours, 62 hours, 64 hours, 66 hours, 68 hours, 70 hours, 72 hours, etc., and it can also be any value within the range of 48 hours to 72 hours.
[0054] Specifically, in this embodiment, titanium dioxide and sodium hydroxide are used as reactants, which are evenly mixed in deionized water and then transferred into a hydrothermal reactor to react at a temperature of 200° C. to 220° C. for 48 h to 72 h. The product is washed with acetic acid to obtain a sodium trititanate precursor.
[0055] S2. Under stirring, the sodium trititanate precursor and the barium source are subjected to a second hydrothermal reaction to obtain fibrous barium titanate;
[0056] In some embodiments, the stirring speed during the second hydrothermal reaction process does not exceed 1000r / min. By stirring during the hydrothermal reaction process, it is helpful to form a better fiber morphology. Exemplarily, the stirring speed during the second hydrothermal reaction process can be 100r / min, 200r / min, 300r / min, 400r / min, 500r / min, 600r / min, 700r / min, 800r / min, 900r / min, 1000r / min, etc., which can also be any value within the range of no more than 1000r / min.
[0057] In some embodiments, the aspect ratio of fibrous barium titanate is 16 to 19; the grain size of fibrous barium titanate is 50 nm to 56 nm. Fibrous barium titanate has a good aspect ratio and grain size, which is beneficial for fibrous barium titanate to construct a capacitor in a cross-sectional dominant direction, thereby achieving a higher capacitance without significantly increasing the volume. Exemplarily, the aspect ratio of fibrous barium titanate can be 16, 17, 18, 19, etc., and it can also be any value in the range of 16 to 19. The grain size of fibrous barium titanate can be 50 nm, 51 nm, 52 nm, 53 nm, 54 nm, 55 nm, 56 nm, etc., and it can also be any value in the range of 50 nm to 56 nm.
[0058] In some embodiments, the barium source includes a barium hydroxide solution, and the molar concentration of the barium hydroxide solution is 0.05 mol / L to 0.2 mol / L. Exemplarily, the molar concentration of the barium hydroxide solution can be 0.05 mol / L, 0.1 mol / L, 0.15 mol / L, 0.2 mol / L, etc., and it can also be any value within the range of 0.05 mol / L to 0.2 mol / L.
[0059] In some embodiments, the molar ratio of barium in the barium source to titanium in the sodium trititanate precursor is 1 to 1.2: 1. For example, the molar ratio of barium in the barium source to titanium in the sodium trititanate precursor can be 1: 1, 1.01: 1, 1.02: 1, 1.03: 1, 1.04: 1, 1.05: 1, 1.06: 1, 1.07: 1, 1.08: 1, 1.09: 1, 1.1: 1, 1.11: 1, 1.12: 1, 1.13: 1, 1.14: 1, 1.15: 1, 1.16: 1, 1.17: 1, 1.18: 1, 1.19: 1, 1.2: 1, etc., and it can also be any value in the range of 1 to 1.2: 1.
[0060] In some embodiments, the temperature of the second hydrothermal reaction is 150° C. to 210° C. For example, the temperature of the second hydrothermal reaction can be 150° C., 160° C., 170° C., 180° C., 190° C., 200° C., 210° C., etc., and can also be any value within the range of 150° C. to 210° C.
[0061] In some embodiments, the time of the second hydrothermal reaction is 0.5h to 16h. Exemplarily, the time of the second hydrothermal reaction can be 0.5h, 1h, 1.5h, 2h, 2.5h, 3h, 3.5h, 4h, 4.5h, 5h, 5.5h, 6h, 6.5h, 7h, 7.5h, 8h, 8.5h, 9h, 9.5h, 10h, 11h, 12h, 13h, 14h, 15h, 16h, etc., and it can also be any value within the range of 0.5h to 16h.
[0062] Specifically, in this embodiment, a sodium trititanate precursor is added to a barium hydroxide solution, and after mixing evenly, the solution is transferred to a reactor, and stirred continuously at a temperature of 150°C to 210°C and a stirring speed of less than 1000 r / min for 0.5h to 16h, and fibrous barium titanate is obtained after washing.
[0063] S3. The fibrous barium titanate is prepared into a slurry and cast into a film to obtain a fiber membrane in which the fibrous barium titanate is oriented;
[0064] In some embodiments, preparing the fibrous barium titanate into a slurry includes ball milling the fibrous barium titanate with an organic solvent, a dispersant, and a plasticizer to obtain a slurry, and the ball milling time of the ball milling is 6 hours to 12 hours. Exemplarily, the ball milling time of the ball milling can be 6 hours, 7 hours, 8 hours, 9 hours, 10 hours, 11 hours, 12 hours, etc., and it can also be any value within the range of 6 hours to 12 hours.
[0065] In some embodiments, the scraper height of the film casting is 80 μm to 120 μm. Exemplarily, the scraper height of the film casting can be 80 μm, 85 μm, 90 μm, 95 μm, 100 μm, 105 μm, 110 μm, 115 μm, 120 μm, etc., and it can also be any value within the range of 80 μm to 120 μm.
[0066] In some embodiments, the casting speed of the cast film is 6 mm / s to 50 mm / s. Exemplarily, the casting speed of the cast film can be 6 mm / s, 10 mm / s, 15 mm / s, 20 mm / s, 25 mm / s, 30 mm / s, 35 mm / s, 40 mm / s, 45 mm / s, 50 mm / s, etc., and it can also be any value within the range of 6 mm / s to 50 mm / s.
[0067] Specifically, in this embodiment, fibrous barium titanate is mixed with an organic solvent, a dispersant, and a plasticizer by ball milling, and a film is prepared by casting to obtain a fiber membrane.
[0068] S4. The fiber membrane is subjected to isostatic pressing and sintering to obtain textured ceramics.
[0069] In some embodiments, the pressure of the isostatic pressing treatment is 65 MPa to 70 MPa. Exemplarily, the pressure of the isostatic pressing treatment can be 65 MPa, 66 MPa, 67 MPa, 68 MPa, 69 MPa, 70 MPa, etc., and can also be any value within the range of 65 MPa to 70 MPa.
[0070] In some embodiments, the heating rate of sintering is 5°C / min to 10°C / min. Exemplarily, the heating rate of sintering can be 5°C / min, 6°C / min, 7°C / min, 8°C / min, 9°C / min, 10°C / min, etc., and can also be any value within the range of 5°C / min to 10°C / min.
[0071] In some embodiments, the sintering temperature is 1200° C. to 1400° C. Controlling the sintering temperature at 1200° C. to 1400° C. is beneficial to improving the dielectric properties of the ceramic cross section oriented with respect to the ceramic surface oriented with the c-axis
[001] and the a-axis
[100] orientation. Exemplarily, the sintering temperature can be 1200° C., 1250° C., 1300° C., 1350° C., 1400° C., etc., and can also be any value within the range of 1200° C. to 1400° C.
[0072] In some embodiments, the sintering holding time is 2h to 3h. Exemplarily, the sintering holding time can be 2h, 2.1h, 2.2h, 2.3h, 2.4h, 2.5h, 2.6h, 2.7h, 2.8h, 2.9h, 3h, etc., and can also be any value within the range of 2h to 3h. It should be noted that the holding time refers to the reaction time after the temperature reaches the set temperature.
[0073] Specifically, in this embodiment, the fiber membrane is cut, laminated, isostatically pressed, debonded, and sintered to obtain a textured ceramic.
[0074] The method uses a hydrothermal ion exchange mechanism to synthesize fibrous barium titanate with a high aspect ratio and small grain size under stirring, and then performs textured casting and sintering. The surface of the textured ceramics obtained presents a c-axis
[001] orientation, and the cross section presents an a-axis
[100] orientation. The dielectric performance of the a-axis cross section is improved at a large rate. In addition, the fibrous barium titanate dielectric material allows capacitors to be constructed in a cross-sectional dominant direction, thereby achieving higher capacitance without significantly increasing the volume, which is particularly suitable for electronic devices with limited space.
[0075] Based on a general inventive concept, an embodiment of the present application further provides a textured ceramic, which is prepared by the method provided above.
[0076] The textured ceramic is prepared based on the above method. The specific steps of the method can refer to the above embodiment. Since the textured ceramic adopts part or all of the technical solutions of the above embodiment, it has at least all the beneficial effects brought by the technical solutions of the above embodiment, which will not be repeated here.
[0077] In some embodiments, the surface of the textured ceramic is preferentially oriented to the c-axis
[001] , and the orientation degree of the c-axis is 15% to 24%; the cross-section of the textured ceramic is preferentially oriented to the a-axis
[100] , and the orientation degree of the a-axis is 15% to 21%.
[0078] Based on a general inventive concept, an embodiment of the present application further provides a capacitor, which includes the textured ceramic provided above.
[0079] The capacitor is realized based on the above-mentioned textured ceramic. The specific content of the textured ceramic can refer to the above-mentioned embodiment. Since the capacitor adopts part or all of the technical solutions of the above-mentioned embodiments, it has at least all the beneficial effects brought by the technical solutions of the above-mentioned embodiments, which will not be repeated here one by one.
[0080] The present application will be further described below in conjunction with specific embodiments. It should be understood that these embodiments are intended only to illustrate the present application and are not intended to limit the scope of the present application. The experimental methods for which specific conditions are not specified in the following examples are usually measured according to national standards. If there is no corresponding national standard, then the conditions recommended by the manufacturer are followed.
[0081] Preparation Example 1
[0082] Add 28.8g of sodium hydroxide and 3g of titanium dioxide to 60ml of deionized water, stir for 1h, transfer the solution to a hydrothermal reactor with polytetrafluoroethylene, and let it stand at 200℃ (stirring rate is 0r / min) for 24h for hydrothermal reaction. Use acetic acid to neutralize the residual alkali in the product until the pH of the product is less than 7. Rinse repeatedly with deionized water until the pH value is 7. After drying at 120℃, sieve with a 40-mesh screen to obtain a sodium trititanate precursor.
[0083] The sodium trititanate precursor was subjected to XRD and SEM tests, and the results were as follows: Figure 2 shown.
[0084] Preparation Example 2
[0085] The sodium trititanate precursor prepared in Preparation Example 1 was added to 150 ml of 0.05 mol / L barium hydroxide solution at a barium-titanium ratio of 1.1. After magnetic stirring for 1 hour, the solution was transferred to a 316 L self-heating stirring kettle. The hydrothermal reaction was carried out at 210 ° C for 30 minutes at a stirring speed of 1000 r / min. The product was soaked in acetic acid for 1 hour and then washed with deionized water until the pH was 7.
[0086] Preparation Example 3
[0087] In this embodiment, except that the concentration of barium hydroxide in Preparation Example 2 is changed from 0.05 mol / L to 0.1 mol / L, the rest of the contents are the same as Preparation Example 2.
[0088] Preparation Example 4
[0089] In this embodiment, except that the concentration of barium hydroxide in Preparation Example 2 is changed from 0.05 mol / L to 0.2 mol / L, the rest of the contents are the same as Preparation Example 2.
[0090] The products of Preparation Example 2, Preparation Example 3 and Preparation Example 4 were subjected to XRD and SEM tests. The results are as follows: Figure 3 and Figure 4 As shown in the figure, at 0.05 mol / L, the product has a relatively consistent nanowire morphology and a large aspect ratio. However, when the concentration of barium hydroxide increases, the nanowire morphology of the product is destroyed and the aspect ratio becomes lower.
[0091] Preparation Example 5
[0092] In this preparation example, except that the stirring speed of 1000 r / min in the reaction process of Preparation Example 2 was changed to 0 r / min, the rest of the contents were the same as Preparation Example 2.
[0093] The product of Preparation Example 5 was subjected to XRD and SEM tests, and the results were as follows: Figure 5 As shown in the figure, when the stirring speed is 0r / min, the nanowire morphology of the product is destroyed, showing a chain-like structure of nanoparticles. Therefore, the hydrothermal reaction under stirring is conducive to maintaining the fibrous morphology.
[0094] Example 1
[0095] A textured ceramic, the preparation process of which is as follows:
[0096] S1: Weigh 15g of the fibrous barium titanate product obtained in Preparation Example 2, place it in a 50ml ball mill, add 125% of the total mass of the matrix powder (an ethanol-ethyl acetate mixture with a mass ratio of 1:2.2), 2.55g of a binder, 1.0625g of a plasticizer, 0.15g of a dispersant, and 52.8g of a zirconium ball, and mix by ball milling for 6h to prepare a mixed slurry;
[0097] S2: The fiber powder was textured using a scraper, and a cast film tape with a film thickness of 12 μm was made by tape casting, wherein the scraper height was 8 μm and the casting speed was 50 mm / s;
[0098] S3: Slice the membrane tape into square membrane sheets of 40 mm*40 mm, stack 60-100 layers, and perform warm water isostatic pressing at a pressure of 65 MPa;
[0099] S4: Use a slicer to cut the embryos after warm water isostatic pressing into samples with a length of 2 mm, a width of 1 mm, and a height of 1 mm;
[0100] S5: The sample is placed in a muffle furnace for sintering at a sintering temperature of 1350°C, a heating rate of 10°C / min, and a holding time of 3h to obtain a textured ceramic.
[0101] Example 2
[0102] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1400° C., the rest of the contents are the same as those of Embodiment 1.
[0103] The textured ceramics provided in Example 1 and Example 2 were subjected to XRD testing, and the results are as follows: Figure 6 and Figure 7 As shown in the figure, it can be seen that there is a difference in the relative height of the XRD (002) (200) diffraction peaks on the surface and in the cross section.
[0104] The
[100]
[001] orientation degree of the surface and cross-section of the textured ceramics provided in Example 1 and Example 2 was tested, and the results are shown in the following table:
[0105]
[0106] It can be seen from the above table that the barium titanate ceramics sintered at 1350°C and 1400°C for 3h present a c-axis
[001] orientation on the surface, and the orientation degree is 15% at 1350°C, and the orientation degree is 24% at 1400°C; the barium titanate ceramics sintered at 1350°C and 1400°C for 3h present an a-axis
[100] orientation in the cross section, and the orientation degree is 21% at 1350°C, and the orientation degree is 15% at 1400°C.
[0107] It can be seen that as the temperature decreases, the orientation degree of the a-axis section tends to further increase, so the surface dielectric constant and interface dielectric constant at lower sintering temperatures are further verified.
[0108] Example 3
[0109] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1220° C., the rest of the contents are the same as those of the embodiment 1.
[0110] Example 4
[0111] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1245° C., the rest of the contents are the same as those of Embodiment 1.
[0112] Example 5
[0113] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1270° C., the rest of the contents are the same as those of Embodiment 1.
[0114] Example 6
[0115] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1295° C., the rest of the contents are the same as those of Embodiment 1.
[0116] Example 7
[0117] In this embodiment, except that the sintering temperature is changed from 1350° C. to 1320° C., the rest of the contents are the same as those of Embodiment 1.
[0118] Comparative Example 1
[0119] In this comparative example, except that the fibrous barium titanate is replaced by commercially available spherical barium titanate powder (300 nm), the rest of the contents are the same as those of Example 1.
[0120] The barium titanate powder provided in Comparative Example 1 was subjected to XRD test, and the results are as follows: Figure 8 As shown in the figure, it can be seen that the barium titanate ceramics prepared from spherical barium titanate powder have no crystal axis orientation, and there is no obvious difference in surface and cross-sectional properties.
[0121] The dielectric constants of the textured ceramic surfaces and cross-sections provided in Example 1, Examples 3 to 7 and Comparative Example 1 were tested, and the results are shown in the following table:
[0122]
[0123]
[0124] From the above table, it can be seen that the a-axis
[100] orientation degree of the ceramic cross section sintered at 1350°C is 21%, but the dielectric property improvement rate can reach 40%.
[0125] Compared with the ceramic surface oriented on the c-axis
[001] , the dielectric properties of the ceramic cross section oriented on the a-axis
[100] can be improved by up to 62%.
[0126] However, the barium titanate ceramics prepared from the spherical barium titanate powder used in Comparative Example 1 have no crystal axis orientation, and have no obvious differences in surface and cross-sectional properties.
[0127] The above are only specific embodiments of the present application and are not intended to limit the present application. For those skilled in the art, the present application may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present application shall be included in the protection scope of the present application.
Claims
1. A method for preparing a textured ceramic, characterized in that: The method comprises: Carrying out a first hydrothermal reaction between a titanium source and a sodium source to obtain a sodium trititanate precursor; Under stirring, the sodium trititanate precursor and the barium source are subjected to a second hydrothermal reaction to obtain fibrous barium titanate; The fibrous barium titanate is prepared into a slurry and cast into a film to obtain a fiber film, wherein the fibrous barium titanate is oriented in the fiber film; The fiber membrane is subjected to isostatic pressing and sintering to obtain textured ceramics.
2. The method for preparing textured ceramics according to claim 1, characterized in that: The stirring speed during the second hydrothermal reaction does not exceed 1000 r / min; and / or The aspect ratio of the fibrous barium titanate is 16 to 19; and / or The grain size of the fibrous barium titanate is 50nm to 56nm.
3. The method for preparing textured ceramics according to claim 1, characterized in that: The titanium source comprises titanium dioxide, and the crystal form of the titanium dioxide comprises at least one of anatase phase, rutile phase or brookite phase; and / or The sodium source comprises a sodium hydroxide solution, wherein the molar concentration of the sodium hydroxide solution is 10 mol / L to 12 mol / L; and / or The temperature of the first hydrothermal reaction is 200°C to 220°C; and / or The time of the first hydrothermal reaction is 48 h to 72 h.
4. The method for preparing a textured ceramic according to claim 1, characterized in that: The barium source comprises a barium hydroxide solution, wherein the molar concentration of the barium hydroxide solution is 0.05 mol / L to 0.2 mol / L; and / or The molar ratio of barium in the barium source to titanium in the sodium trititanate precursor is 1 to 1.2:1; and / or The temperature of the second hydrothermal reaction is 150°C to 210°C; and / or The time of the second hydrothermal reaction is 0.5h to 16h.
5. The method for preparing textured ceramics according to claim 1, characterized in that: The step of preparing the fibrous barium titanate into a slurry comprises ball milling the fibrous barium titanate, an organic solvent, a dispersant, and a plasticizer to obtain a slurry, and the ball milling time of the ball milling is 6 hours to 12 hours.
6. The method for preparing textured ceramics according to claim 1, characterized in that: The scraper height of the film casting is 80 μm to 120 μm; and / or The casting speed of the cast film is 6 mm / s to 50 mm / s.
7. The method for preparing textured ceramics according to claim 1, characterized in that: The isostatic pressure treatment pressure is 65MPa to 70MPa; and / or The heating rate of the sintering is 5°C / min to 10°C / min; and / or The sintering temperature is 1200°C to 1400°C; and / or The sintering heat preservation time is 2h to 3h.
8. A textured ceramic, characterized in that: The textured ceramic is prepared by the method according to any one of claims 1 to 7.
9. The textured ceramic according to claim 8, characterized in that: The surface of the textured ceramic has a preferred orientation of c-axis [001], and the orientation degree of c-axis is 15% to 24%; and / or The cross-section of the textured ceramic is preferentially oriented to the a-axis [100], and the orientation degree of the a-axis is 15% to 21%.
10. A capacitor, characterized in that: The capacitor comprises the textured ceramic of any one of claims 8 to 9.